Gugatan Perbuatan Melawan Hukum Karena Standar Pelayanan Tambahan Sebelum Penerbangan bagi Penumpang Berkebutuhan Khusus Lanjut Usia yang Mengakibatkan Penumpang Meninggal Dunia: Analisis Hukum Putusan Nomor 523/Pdt.G/2023/Pn Mnd - Raden Sihar Martogi Sinambela; Appe Hutauruk; Hotman Sinambela; Mardiman Sane; Setia Jaya; Fendi Maruba Parlindungan Hutahaean (Jurnal Hukum Lex Generalis, 2025)
This study analyzes the lawsuit for Unlawful Acts (PMH) related to additional service standards for elderly passengers with special needs resulting in death, based on Decision Number 523/Pdt.G/2023/PN Mnd. The main focus of the study is to evaluate the legal responsibility of airlines in providing pre-flight services and the basis for the judge's considerations in deciding the case. Using a normative legal research method with a case approach, the results of the study indicate that the airline's non-compliance with standard operating procedures for serving passengers with special needs constitutes a form of negligence that fulfills the elements of PMH according to Article 1365 of the Civil Code. [REVISI] This study also examines airline obligations under Law Number 1 of 2009 on Aviation and applicable passenger protection regulations. Decision Number 523/Pdt.G/2023/PN Mnd established that the airline was proven to have committed unlawful acts and was ordered to provide compensation to the plaintiff.